Pengaruh Sikap Profan terhadap Paradigma Masyarakat Beragama Perspektif Emile Durkheim - Khair, Nurul (Jurnal Sosiologi Agama, 2020)
In recent developments the profane attitude produces fictional knowledge in understanding religious symbols, as a result religion is not seen as something sacred but a medium to achieve goals based on passion. The development of this paradigm, due to the power of human perception in understanding religious symbols. The power of perception increases the power of human imagination involving impulse in the self. This paper is an analysis of Emile Durkheim’s thoughts about the profane attitude towards the paradigm of religious society. This paper aims to determine the influence of profane attitudes in shaping the framework of religious communities and providing solutions to the low paradigm of religious communities in understanding religious symbols. Aqliyah approach is a fundamental solution to overcome these problems. Durkheim explained that the process of uniting nature, humans, and God was due to the work process of reason, as the application of totem societies in understanding religious symbols. The implication, is to increase human existence in the religious frame and provide solutions as a form of attention to the lack of human knowledge in understanding the concept of religion